Analysis of the effects of bench-scale cell culture platforms and inoculum cell concentrations on PSC aggregate formation and culture - Iworima, Diepiriye G.; Baker, Robert K.; Piret, James M.; Kieffer, Timothy J. (Frontiers in Bioengineering and Biotechnology, 2023)
Human pluripotent stem cells (hPSCs) provide many opportunities for application in regenerative medicine due to their ability to differentiate into cells from all three germ layers, proliferate indefinitely, and replace damaged or dysfunctional cells. However, such cell replacement therapies require the economical generation of clinically relevant cell numbers. Whereas culturing hPSCs as a twodimensional monolayer is widely used and relatively simple to perform, their culture as suspended three-dimensional aggregates may enable more economical production in large-scale stirred tank bioreactors. To be more relevant to this biomanufacturing, bench-scale differentiation studies should be initiated from aggregated hPSC cultures. To this end, we compared five available bench-scale platforms for generating undifferentiated cell aggregates of human embryonic stem cells (hESCs) using AggreWell TM plates, low attachment plates on an orbital shaker, roller bottles, spinner flasks, and vertical-wheel bioreactors (PBS-Minis). Of these formats, the AggreWell TM system had the highest aggregation yield. The initial cell concentrations had an impact on the size of aggregates generated when using AggreWell TM plates as well as in roller bottles. However, aggregates made with low attachment plates, spinner flasks and PBS-Minis were similar regardless of the initial cell number. Aggregate morphology was compact and relatively homogenously distributed in all platforms except for the roller bottles. The size of aggregates formed in PBS-Minis was modulated by the agitation rate during the aggregation. In all cell culture platforms, the net growth rate of cells in 3D aggregates was lower (range: -0.01 -0.022 h -1 ) than cells growing as a monolayer (range: 0.039 -0.045 h -1 ). Overall, this study describes operating ranges that yield high-quality undifferentiated hESC aggregates using several of the most commonly used bench-scale cell culture platforms. In all of these systems, methods were identified to obtain PSC aggregates with greater than 70% viability, and mean diameters between 60 and 260 µm.